HUBUNGAN ANTARA NOVELTY-CENTERED BUSINESS MODEL DESIGN (NBMD) DAN KINERJA OPERASIONAL: INTEGRASI EXTERNAL SEBAGAI VARIABEL MEDIASI - Yusa, Atika; Ammar, Izmi wardah; Riyansha, Ridho; Sari, Wati Indah; Candra, Yoni; Zaitul, Zaitul (Bussman Journal : Indonesian Journal of Business and Management, 2025)
This study aims to analyze the relationship between Novelty-Centered Business Model Design (NBMD) and operational performance by considering the mediating role of external integration in the self-service retail sector in Padang City. The background of this research departs from the challenges faced by supermarkets in facing digital competition and changes in consumer behavior, which demand innovation in business models as well as cross-organizational collaboration. This study uses a quantitative approach with the Partial Least Squares Structural Equation Modeling (PLS-SEM) method on data from 35 respondents consisting of owners, store managers, and supermarket managers. The results showed that NBMD had a positive and significant effect on external integration, but no significant influence was found either directly or indirectly from NBMD and external integration on operational performance. Thus, external integration has not been proven to be a mediator in the relationship between NBMD and operational performance. The study concludes that novelties in business model design tend to strengthen external collaboration, but the impact on operational performance has not been seen directly. The practical implications of these results emphasize the importance of improving the quality of the implementation of external integrations as well as other internal factors in order for business model innovation to produce optimal operational performance